A CRIMINAL LAW REVIEW OF CYBERBULLYING AS A FORM OF DIGITAL CRIME - Giannini Oktobellini Henrik; Ardiyanti Aris; Lilis Suryani; Sunardi Purwanda; Phirer (PT. Radja Intercontinental Publishing, 2026)
This study aims to analyze the qualifications of cyberbullying as a criminal act within the digital crime family and examine the effectiveness of positive legal regulations in Indonesia in ensnaring perpetrators. The research method used is a normative one with a statute approach and a conceptual approach. The data used is secondary data sourced from primary and secondary legal materials, which are then analyzed qualitatively. The results of the study indicate that cyberbullying has fulfilled the elements of a digital crime (cybercrime) and is regulated in several regulations, particularly the Electronic Information and Transactions Law (UU ITE) and the Criminal Code (KUHP). However, law enforcement still faces normative challenges, such as the interpretation of certain articles (rubber articles) and complex digital evidence. Regulation harmonization and a more specific formulation of crimes regarding cyberbullying are needed to provide legal certainty and optimal protection for victims.